Preparation of Pb(II) ion-imprinted polymers and their application in selective removal from wastewater - Xianglong Ao; Hongzhi Guan (Adsorption Science & Technology)
A novel hydrophilic Pb(II) ion-imprinted polymer (Pb(II)-IIP) was synthesized using lead ion as a template ion, 2-(allyl sulfur) nicotinic acid as functional monomer by precipitation polymerization method. The adsorption capacity of Pb(II)-IIP to Pb(II) was saturated at 16 min, and the adsorption process is consistent with the quasi-second-order kinetic adsorption model. The optimum adsorption capacity of Pb(II)-IIP was 29.67 mg/g, about triple than Pb(II)-NIP, and the adsorption is in accordance with the Langmuir isothermal model, which indicates that it is dominated by single layer chemical adsorption. X-ray Photoelectron Spectroscopy (XPS) and Energy Dispersive Spectrometer (EDS) data confirm that the chelate ratio of Pb(II) to 2-(allylthio) nicotinic acid is 1:2. In the presence of competing ions, the adsorption capacity of Pb(II)-IIP to Pb(II) is much larger than that of other ions, which indicates that Pb(II)-IIP is less disturbed by competitive ions. The experiment of application of practical wastewater shows that Pb(II)-IIP has a Pb(II) removal rate of 97.2% or more in practical industrial wastewater, which is in accordance with national emission standards. It is proved that Pb(II)-IIP is an effective material to remove Pb(II) in industrial wastewater.